Evaluación de consorcio microbiano aerobio para la degradación de materia orgánica en aguas residuales en extractora de aceite vegetal AEXAV Quininde - Ponce Zambrano, Andrés Arturo (2019)
The present work consisted in evaluating the removal of the organic matter using microbial consortiums subtilis, licheniformis and plantarum in wastewater of the company AEXAV of African palm fine oil, the same one that began with the application of the bibliographic method which served to investigate issues Relevant studies, different definitions of authors. The field service method to obtain information from the respective samples, the experimental quantitative method that allowed to evaluate the effect of the microbial consortium. Descriptive to perform the respective analysis of the results obtained, a composite sampling was performed to determine physical-chemical parameters (chemical demand for oxygen, oxygen biochemical demand, total solids, oils and fats, dissolved oxygen) of the effluent. A completely randomized design was applied with five treatments with two family types, Bacillus and Lactobacillus with three replicates 15 experimental units. A removal of BOD5 85%, COD 99%, ST 36%, Oils and Fats 84% was obtained, of the five treatments it could be observed that the best was the combination of 3 autochthonous bacteria of the ESPAM 'MFL'. So it is concluded that the most efficient treatment is T4 composed of subtilis, licheniformis and plantarum, since it helps to eliminate the organic load in the effluent that is generated in the palm extractor.